Grass dominance drives rhizospheric bacterial communities in a desertic shrub and grassy steppe highland - Menoyo, Eugenia (2017)
The rhizosphere is a dynamic root-soil interface characterized by interactions between soil microorganisms and roots. These interactions can be potential drivers of the structure of the plant and bacterial communities in desertic shrub and grassy steppe highlands. We analyzed the relationships of rhizospheric bacterial density and occurrence (presence/absence) with dominance degree of grasses and soil properties in Argentina's Puna ecosystem. Rhizospheric bacterial density was low and showed a strong relationship with the dominance degree of grasses without any significant influence from the soil or other vegetation variables. In addition, we determined rhizospheric bacterial occurrence with PCR-DGGE analysis of the 16S rRNA genes. Actinobacteria, Firmicutes and Proteobacteria were the predominant bacterial groups associated to the rhizosphere of grasses. In Puna highlands, the rhizospheric bacterial community appear driven by the dominance degree of grasses with little influence from other biotic or abiotic factors. We suggest that tight plant-bacterial interactions have evolved in these harsh environments that promote some level of grass dominance and maintain the diversity of the rhizospheric bacterial communities.